Geriatrics education is associated with positive attitudes toward older people in internal medicine residents: A multicenter study. Issue 2 (March 2015) - Tufan, Fatih; Yuruyen, Mehmet; Kizilarslanoglu, Muhammet Cemal; Akpinar, Timur; Emiksiye, Sirhan; Yesil, Yusuf; Ozturk, Zeynel Abidin; Bozbulut, Utku Burak; Bolayir, Basak; Tasar, Pinar Tosun; Yavuzer, Hakan; Sahin, Sevnaz; et al.
Abstract Objective The number of older people is growing fast in Turkey. In this context, internal medicine residents and specialists contact older people more frequently. Thus, healthcare providers' knowledge and attitudes toward older people is becoming more important. Studies that specifically investigate internal medicine residents' attitudes toward the elderly are scarce. We aimed to investigate the attitudes of internal medicine residents toward older people. Methods This cross-sectional multicenter study was undertaken in the internal medicine clinics of six university state hospitals that provide education in geriatric care. All internal medicine residents working in these hospitals were invited to participate in this questionnaire study between March 2013 and December 2013. We recorded the participants' age, sex, duration of internal medicine residency, existence of relatives older than 65 years, history of geriatrics course in medical school, geriatrics rotation in internal medicine residency, and nursing home visits. Results A total of 274 (82.3%) of the residents participated in this study, and 83.6% of them had positive attitudes toward older people. A geriatrics rotation during internal medicine residency was the only independent factor associated with positive attitudes toward the elderly in this multivariate analysis. A geriatrics course during medical school was associated with positive attitudes in the univariate analysis, but only tended to be so in the multivariate analysis. Conclusion Geriatrics rotation during internal medicine residency was independently associated with positive attitudes toward older people. Generalization of geriatrics education in developing countries may translate into a better understanding and improved care for older patients.